Quantitative image indices in ultrasonic diagnostics of inbomogeneous materials - CHIVERS, Robert C. (Archives of Acoustics, 1981)
The use of a commercial image analyser for dimensional analysis of discrete features of ultrasonic images has been described previously. The present paper reports a pilot study on the use of such an analyser for quantitative analysis of the diffuse texture of an ultrasonic image of an inhomogeneous material. Althought such a use may provide valuable arbitrary diagnostic indices, a procedure is outlined by which such indices may be used in conjunction with visual perceptual studies to optimise the display or to investigate the physical mechanisms of image formation.